2006
DOI: 10.1115/1.2437800
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Application of a 2-DOF Planar Parallel Mechanism

Abstract: This paper deals with the optimal kinematic design, dynamic analysis, and application of a 2 degree of freedom (2-DOF) planar parallel mechanism. In the optimal kinematic design phase, the singularities and workspace are investigated, and the optimal kinematic parameters of the mechanism are achieved by minimizing a global and comprehensive conditioning index. The Newton–Euler method is employed to derive the inverse dynamic model. Dynamic simulations show that the inertia force of moving parts is an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…A 2-DOF parallel machine tool in Refs. [22,23] can be synthesized from TG with Q+2T+6B in Fig. 14(b).…”
Section: Application Examples Of Tg and Dtgmentioning
confidence: 99%
“…A 2-DOF parallel machine tool in Refs. [22,23] can be synthesized from TG with Q+2T+6B in Fig. 14(b).…”
Section: Application Examples Of Tg and Dtgmentioning
confidence: 99%
“…However, these manipulators have smaller workspace. In addition, works on singularities of parallel manipulators [1][2][3][4] show that static singularities (which are completely absent in open-chain serial manipulators) appear within the workspace with continuous region thereby rendering the manipulator uncontrollable in some regions of the workspace. It has been shown that actuation redundancy can be an effective solution for eliminating singularities in parallel manipulator designs and thus improving their performances [5].…”
Section: Introductionmentioning
confidence: 97%
“…Parallel manipulators have drawn continuous interest in both academia and industry in recent years [1]. This is due to their favorable characteristics such as low mobile masses, high stiffness, acceptable accuracy, and so on.…”
Section: Introductionmentioning
confidence: 99%